Early diagnosis of hearing impairment in newborns - Prażmowska, Barbara; Dziubak, Małgorzata; Leszczyńska, Agnieszka; Tomasik, Tomasz (European Journal of Clinical and Experimental Medicine, 2010)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim of the thesis: The sense of hearing plays a vital role in our interactions with the environment, and has an important influence on the psychomotor development of the child. The all-Poland hearing impairment screening programme, carried out in children suspected of this malfimc-tion, allows for an early diagnosis and helps to define the risk groups for hearing impairment. It is early diagnosis, followed by systematic treatment and rehabilitation, that condition the child's correct intellectual, emotional, cognitive, social and, finally, professional, development. This thesis aims to examine the connection between risk factors for hearing impairment, and the identification of the infant group suspected of this condition. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and method: The screening tests were conducted in a group of 123 infants (born both pre-maturely and at term), with risk factors for hearing impairment, hospitalised at the Neonatal Pathology and Intensive Care Unit of the Children's University Hospital in Krakow Medical documentation nos studied for the purposes of the research. Statistical analysis was applied to the results of the research. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results: The screening test was carried out in a group of 48 infants born prematurely and 75 infants born at term. For 60% of the premature infants and 78% of the term infants, the results fell within the "normal" range. It nos observed that there mos a general positive correlation between the "abnormal" hearing test results and the number of risk factors for hearing impairment in the patients examined (Kendall tau coefficient at -0,32). In premature infants none of the risk factors was predictive for the results of the hearing test. In term babies the strongest risk factor nos artificial ventilation lasting longer that day days, as well the Apgar score below four in one minute, and below six in five minutes after birth. <p class="rtejustify" style="box-sizing: border-box; margin: 0px; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusions: Screening tests for hearing impairment, carried out in all infants, not only those hos-pitalised at Neonatal Intensive Care Units, allow for an early diagnosis of hearing defects and their treatment, which helps to prevent numerous figure health problems.